The chain-mediation pathway of gender regarding academic delay of gratification in college students is regulated by anxiety/depressive mood and prospective memory - Jiao, Chen-Yang; Song, Xun; Shao, Wen-Yi; Feng, Lin-Pu; Jiao, Dong-Liang (Frontiers in Psychology, 2022)
Objective: This study investigated the relationship between gender and academic delay of gratification (ADOG) in college students and explored the mediating roles of anxiety/depressive mood and prospective memory to provide a theoretical intervention approach based on internal mechanisms. Methods: Random cluster sampling was conducted on 609 students from three universities situated in the Province of Anhui, China with the use of data from several questionnaires: the general information questionnaire, Generalized Anxiety Disorder Scale, Patient Health Questionnaire, Prospective and Retrospective Memory (PRM) Questionnaire, and ADOG Scale. Results: The females’ anxiety and depression levels were lower than that of the males, while the female PRM and ADOG performance improved when compared to that of the males. Anxiety and depression were negatively correlated with PRM and ADOG, respectively, whereas the PRM and ADOG data demonstrated a positive correlation. Depression/anxiety and prospective memory also played a chain intermediary role between gender and ADOG. Conclusions: Gender not only directly affects college students’ ADOG, but it also has indirect effects through depression/anxiety and prospective memory. Therefore, it is very important to treat students' mental health differently according to gender to improve prospective memory and delayed academic satisfaction.